Pelatihan Register Jurnal Ilmiah Ke Penerbit Open Journal System (OJS) pada tenaga pendidik di SMP N 4 Siak Hulu Kabupaten Kamp - HADIYATI, HADIYATI; FATKHURAHMAN, FATKHURAHMAN (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2017)
Abstract: Analysis of partner situation, teachers as professional educators, especially for civil servant teachers are required to improve the rank and position that most of the time have never received training registers to OJS publishers. One of the requirements of taking care of rank and becoming a teacher constraint is writing articles and published to scientific journals. While teachers do not have knowledge and so far most teachers have not received training how to register to scientific journals. Training to teachers is given, training is targeted to teachers able to register their articles to OJS scientific journal (open journal system), in addition to easily accessed via internet and journal entry system more transparent. The method of implementation is to use lecture and question and answer methods. Based on the results of dedication to the community, it can be explained that there is a change of knowledge, understanding and ability of the participants in attending the existing training. Although still not maximal changes in the ability to register, but some existing teachers who managed to register. Keywords: Register Scientific Journal, OJS